Changing Face of Wood Science in Modern Era: Contribution of Nanotechnology - Mishra, Pawan Kumar; Giagli, Kyriaki; Tsalagkas, Dimitrios; Mishra, Harshita; Talegaonkar, Sushma; Gryc, Vladimír; Wimmer, Rupert (Recent patents on nanotechnology, 2018)
BACKGROUND: Wood science and nanomaterials science interact together in two different aspects; a) fabrication of lignocellulosic nanomaterials derived from wood and plant-based sources and b) surface or bulk wood modification by nanoparticles. In this review, we attempt to visualize the impact of nanoparticles on the wood coating and preservation treatments based on a thorough registration of the patent databases. METHOD: The study was carried out as an overview of the scientifically most followed trends on nanoparticles utilization in wood science and wood protection depicted by recent universal filed patents. This review is exclusively targeted on the solid (timber) wood as a subject material. RESULTS: Utilization of mainly metal nanoparticles as photoprotection, antibacterial, antifungal, antiabrasive and functional component on wood modification treatments was found to be widely patented. Additionally, an apparent minimization in the emission of volatile organic compounds (VOCs) has been succeeded. CONCLUSION: Bulk wood preservation and more importantly, wood coating, splay the range of strengthening wood dimensional stability and biological degradation, against moisture absorption and fungi respectively. Nanoparticle materials have addressed various issues of wood science in a more efficient and environmental way than the traditional methods. Nevertheless, abundant tests and regulations are still needed before industrializing or recycling these products.
Keywords: hydrofobní a hydrofilní interakce; VOCs; ultrafialové záření; Formaldehyde; antiinfekční látky; Wood; surface treatments; nanotechnologie; povrchové vlastnosti; Anti-Infective Agents; Nanotechnology; wood modification; Hydrophobic and Hydrophilic Interactions; Surface Properties; wood coatings; formaldehyd; Patent; dřevo; Ultraviolet Rays; těkavé organické sloučeniny; metal nanoparticles; Volatile Organic Compounds